Psychological Foundations Educational Leadership. Approach to the Problem - Lebid, Nelia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article indicates leadership qualities in the context of transformational processes in the society associated with innovations, including in education. The concept of educational leadership as a type of social activity, which is covered in three interrelated aspects: leadership in education, leadership for education, leadership of education is analyzed. The phenomenon of leadership as a social and psychological phenomenon in higher education is considered from the perspective of the analysis of three main structural elements: the person with leadership potential, groups of followers, factors of social environment. Theoretical analysis of the psychological foundations of educational leadership allowed identifying the problems for further research.